2010
DOI: 10.1186/1471-2474-11-278
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of the shoulder in asymptomatic elderly subjects with diabetes

Abstract: BackgroundThe prevalence of rotator cuff tears increases with age and several studies have shown that diabetes is associated with symptomatic shoulder pathologies. Aim of our research was to evaluate the prevalence of shoulder lesions in a population of asymptomatic elderly subjects, normal and with non insulin - dependent diabetes mellitus.MethodsThe study was performed on 48 subjects with diabetes and 32 controls (mean age: 71.5 ± 4.8 and 70.7 ± 4.5, respectively), who did not complain shoulder pain or dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 57 publications
6
70
0
2
Order By: Relevance
“…Our findings confirmed that patients with diabetes, regardless of insulin use, had a higher risk of developing rotator cuff diseases. Our findings are in accord with previous imaging studies showing that degenerative changes of rotator cuff tendon were more commonly observed by sonography in patients with diabetes than in controls3.…”
supporting
confidence: 93%
“…Our findings confirmed that patients with diabetes, regardless of insulin use, had a higher risk of developing rotator cuff diseases. Our findings are in accord with previous imaging studies showing that degenerative changes of rotator cuff tendon were more commonly observed by sonography in patients with diabetes than in controls3.…”
supporting
confidence: 93%
“…3 Tears were divided into small, large, or massive when the distance between the ends was less than 1 cm, more than 1 cm but less than 3 cm, and more than 3 cm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…3 For the purposes of the present study, analysis was restricted to the supraspinatus and infraspinatus tendons, and only full-thickness tears (FTTs) were taken into account.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the measurement of supraspinatus tendon thickness was found reliable. [16][17][18] The ultrasonographic diagnosis has the potential for becoming a valuable aid to the clinician in allowing confident diagnosis, and it enables to follow up treatment efficiency. [19][20][21][22] Rehabilitation of the patients with SIS is a complex process that requires a comprehensive evaluation and multifactorial treatment program.…”
mentioning
confidence: 99%